Subcutaneous phaeohyphomycosis caused by Lasiodiplodia theobromae and successfully treated surgically - Summerbell, R.C.; Krajden, S.; Levine, R.; Fuksa, M.
While visiting Jamaica, a 50-year-old woman stumbled on an outdoor wooden staircase and sustained an injury to the right leg. The wound was cleaned topically and the patient was given antibacterial therapy. Five weeks later, in Canada, she presented with an ulcer at the injury site. An excisional biopsy showed copious broad, septate, melanized fungal filaments penetrating into tissue. Culture yielded a nonsporulating melanized mycelium. The isolate was strongly inhibited by cycloheximide and benomyl but grew at 378C. After 16 weeks cultivation on modified Leonian's agar at 258C, it developed pycnidia characteristic of Lasiodiplodia theobromae, a common tropical phytopathogen mainly known previously as a rare agent of keratitis and onychomycosis in humans. The patient was not given antifungal chemotherapy, and the ulcer, which had been broadly excised in the biopsy procedure, ultimately resolved after treatment with saline compresses. The six-month follow-up showed no sign of infection. This case, interpreted in light of previously reported cases, shows that on rare occasions L. theobromae is able to act as an agent of subcutaneous phaeohyphomycosis and that, when this occurs, debridement alone may be sufficient to eradicate it.
Keywords: BOTRYODIPLODIA; BOTRYOSPHAERIA RHODINA; LASIODIPLODIA; PHAEOHYPHOMYCOSIS; TROPICAL MEDICINE